An equilibrium search model of the informal sector - Eliane Badaoui; Eric Strobl; Frank Walsh (University College Dublin, UCD School of Economics, 2006)
We use an equilibrium search framework to model a formal- informal sector labour market where the informal sector arises endogenously. In our model large firms will be in the formal sector and pay a wage premium, while small firms are characterised by low wages and tend to be in the informal sector. Using data from the South African labour force survey we illustrate that the data is consistent with these predictions.
hdl:10197/955
Keywords: 330; Arbeitsmarkt; Informeller Sektor; Lohnniveau; Ökonometrisches Modell; Südafrika